Effects of Glucomannan and Inulin Supplementation on Glial Inflammation in Mice Fed a High-Fat, High-Sucrose Diet - Nita Kurniawati; Cristoforus Aji Pamungkas; Shanea Veronica Jovangka; Bernadette Dian Novita; Yudy Tjahjono; Hendy Wijaya; Irene Lingkan Parengkuan; FX Himawan Haryanto Jong; Pauline Meryana; Arya Pandhu Wiratama (Universitas Airlangga, 2026)
Highlight: Inulin and glucomannan modulated IL-6 and IL-10 in HFHS-fed mice. Inulin reduced IL-6, while combined fiber modulated IL-10 expression. ABSTRACT Introduction: A HFHS (high-fat, high-sucrose) diet induces neuroinflammation through dysregulated glial cell signaling and persistent low-grade inflammation, characterized by elevated IL-6/interleukin-6 and decreased IL-10/interleukin-10 levels. Dietary fibers including glucomannan and inulin are reported to modulate gut microbiota and inflammatory responses; however, their effects on HFHS-induced neuroinflammation remain unclear. Objective: This study examined the effects of glucomannan, inulin, and their joint administration on IL-10 and IL-6 expression in glial cells of mice fed an HFHS diet. Methods: As many as 15 male C57BL/6 mice were allocated at random to five groups: control (AQ), HFHS (KN), HFHS plus glucomannan (GO), HFHS plus inulin (IO), as well as HFHS plus a mixture of inulin and glucomannan (IG), with three animals in each group. During the intervention period, fiber supplements were administered orally. IL-10 and IL-6 expression in glial cells was evaluated through immunohistochemistry and quantified by mean gray value (MGV) analysis using ImageJ software. Statistical analysis was executed via one-way ANOVA with a p < 0.05 significance level. Results: IL-6 expression was lowest in the control (AQ) group, whereas the combination treatment (IG) showed reduced IL-6 expression relative to the other HFHS-fed groups. The IG group also exhibited the lowest IL-10 expression among all groups. These findings suggest that the combined supplementation may attenuate pro-inflammatory IL-6 expression but does not appear to enhance the anti-inflammatory IL-10 response. Conclusion: Combined supplementation with glucomannan and inulin reduced IL-6 expression within HFHS-fed mice but did not increase IL-10 expression. These findings indicate that dietary fiber supplementation may selectively modulate inflammatory pathways associated with diet-induced neuroinflammation.